التفریق القضائي (Journal of the College of Education for Women, 2019)
Divorce and that was really the man used when he wants and his solebut it is not only mediated by the judiciary to be introduced to the dispute thatoccurred between the couple before the sentencing differentiating this as wellas to make his endeavors for the realization of each of the spouses gmtyoffended someone used it shall compensation.